Adefovir- or Lamivudine-Induced Renal Tubular Dysfunction after Liver Transplantation. Issue 38 (September 2015) - Lee, Jae Geun; Lee, Juhan; Lee, Jung Jun; Song, Seung Hwan; Ju, Man Ki; Choi, Gi Hong; Kim, Myoung Soo; Choi, Jin Sub; Kim, Soon Il; Joo, Dong Jin; Wang., Hsueh
<x xml:space="preserve">Abstract</x> Abstract To reduce hepatitis B virus reinfection after liver transplantation (LT), patients often receive antihepatitis B immunoglobulin (HBIG) alone or combined with antiviral nucleoside/nucleotide analogs (NUCs); however, proximal renal tubular dysfunction (RTD) that was induced by NUCs in liver recipients was rarely reported. Here, we analyzed RTD and renal impairment (RI) following adefovir (ADV) and lamivudine (LAM) treatment in liver recipients. We retrospectively reviewed medical records of patients treated with HBIG alone (group 1, n = 42) or combined with ADV or LAM (group 2, n = 21) after LT. We compared RTD and RI incidence during the 12 months after LT. An RTD diagnosis required manifestation of at least 3 of the following features: hypophosphatemia, RI, hypouricemia, proteinuria, or glucosuria. No significant differences were observed regarding sex, age, donor type, model of end-stage liver score, and estimated glomerular filtration rate at pre-LT between the 2 groups. Hepatitis B virus recurrence within 12 months was 4.8% in both groups (P = 1.000); however, the RTD incidence was 0% in group 1 and 19.0% in group 2 (P = 0.010). RI occurrence did not differ between the groups. The only risk factor for RI was HBIG administration combined with both LAM and ADV (odds ratio 11.27, 95% confidence interval 1.13–112.07, P = 0.039, vs HBIG alone). RTD occurred more frequently in patients treated with HBIG combined with LAM or ADV compared with HBIG alone. Thus, LAM or ADV therapy can induce RTD after LT, and when administered, liver recipients should be monitored.